TEOLOGI PLURALIS: Studi Living Islam di Dusun Gunung Sari, Sambirejo, Prambanan, Sleman, Yogyakarta - Muzairi Muzairi; Muhammad Arif (UIN Sunan Kalijaga Yogyakarta, 2018)
Although large-scale religious conflicts such as the Ambon and Poso cases have ended, it does not mean that Indonesia has been able to get out of the danger zone of violence, which is based on religion. One of the latent dangers of religious-based violence can be found in Gunung Sari, Sambirejo, Prambanan, Sleman, Yogyakarta, in which there are three Islamic groups: NU, Muhammadiyah, and Islam-Tawheed. Each group member has a different view, from religious rituals to their social interactions, even physical conflicts have occurred between them. For this reason, we are inte- rested in doing research as well as living there. Based on our research, it was found that no longer true of what Ahmad Salehudin had described in his previous research, today they appreciate religious differences and views about religion among them. Slowly but surely, they have practiced a pluralist theology (living Islam).